A progressão Temática em resumos de artigo científico: uma análise sistêmica- funcional - Fernando Suarez de Oliveira (2017)
The current academic environment in Brazil and in the world demands the development of deeper studies concerning academic writing. Considering the constantly growing needs of this environment in relation to the quality of the material published, we see institutions becoming more and more demanding in terms of the works that are produced by their researchers. Considering that research article abstracts are an important genre in the academic field, this thesis aims at adding up to the studies of language usage and description, by verifying the patterns of thematic progression that are more frequent in texts of this genre and the cohesive elements that guarantee this progression, as well as its contribution to the structural organization of those texts of this genre. This research was carried out by adapting the methodology applied by Hawes (2015), with the compilation of a set of abstracts collected by the Corpus Acadêmico do Português Brasileiro (CAPB). Two abstracts belonging to each area defined by CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior) were collected, which led to the study of 18 abstracts in total. The analysis was developed by, first, reading the texts and identifying all the themes in them, and, second, by observing the patterns of thematic progression and the cohesive devices used in theses processes, which allowed the elaboration of a schema for each text. With these schemas in hand, it was possible to evaluate the structure of the abstracts in terms of their thematic progression. The results show that essentially a random pattern was observed in the analysis of the abstracts, among which the most frequent was the linear progression. Furthermore, it was possible to observe that the cohesive devices established by Halliday and Matthiessen (2014) were the ones responsible for the progression, from which the most frequent was the lexical cohesion. It was considered that this was the most frequent since overall in academic writing the target public is very specific, e. g. researchers and professionals of the area, in a way that it is possible to use the lexicon of each area of knowledge in a more varied manner, leading to a constant use of collocates. In addition, the thematic progression was considered to have a close relation to the structure of the abstracts, for very frequently it was observed that there was a break in the thematic progression in the transition between some of the moves in the texts, for instance, from Context to Purpose and from Results to Conclusion. This study showed that the patterns of thematic progression are an important contribution to the cohesion of abstracts, since, by means of cohesive devices, they guarantee the structure of the text, also helping the organization of its structure, revealing the moment when there is a change in the communicative purpose in the development of the text.